Deli Maatschappij's Contribution to the Transformation of East Sumatera, 1869-1940s (Paramita: Historical Studies Journal, 2021)
Abstract: Indonesian historiography notes that East Sumatra is known for its poor treatment of plantation companies towards their workers. Nevertheless, the presence of plantation companies also causes East Sumatra to grow rapidly.  This study aims to uncover the contributions provided by Deli Maatschappij in transforming East Sumatra into a more modern one and its impacts on plantation communities and local communities. The study uses critical historical methods that include heuristic activities, source criticism, interpretation, and historiography. The approach of social science is used as an analytical tool. The sources used in this study include the Deli Maatschappij memorial books, magazines, and other sources from the period. The results showed that Deli Maatschappij had a significant contribution to East Sumatra's transformation process, primarily related to its role in changes in transportation systems, health services, water supply, and education. It can be concluded that the community also had a positive impact from these changes. Abstrak: Historiografi Indonesia mencatat bahwa Sumatera Timur dikenal dengan perlakuan buruk perusahaan perkebunan terhadap pekerjanya. Kendati demikian, kehadiran perusahaan perkebunan juga menyebabkan Sumatera Timur berkembang pesat. Studi ini bertujuan untuk mengungkap kontribusi yang diberikan oleh Deli Maatschappij dalam mengubah Sumatera Timur menjadi lebih modern dan dampaknya terhadap masyarakat perkebunan dan masyarakat lokal. Penelitian ini menggunakan metode sejarah kritis yang meliputi kegiatan heuristik, kritik sumber, interpretasi, dan historiografi. Pendekatan ilmu sosial digunakan sebagai alat analisis. Sumber yang digunakan dalam penelitian ini antara lain buku peringatan Deli Maatschappij, majalah, dan sumber lain dari periode tersebut. Hasil penelitian menunjukkan bahwa Deli Maatschappij memiliki kontribusi yang sangat signifikan terhadap proses transformasi di Sumatera Timur terutama terkait perannya dalam perubahan sistem transportasi, pelayanan kesehatan, penyediaan air bersih, dan pendidikan. Dapat disimpulkan bahwa masyarakat juga merasakan dampak positif dari perubahan tersebut.